BEHAVIORAL IMPLICATIONS OF AI-SUPPORTED MANAGEMENT ACCOUNTING INFORMATION ON MANAGERIAL JUDGEMENT AND PERFORMANCE - Christina Sososutiksno; Irga Anugrah Safira Harahap; Nurul Amalia Ali Slamat (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
The development of artificial intelligence has brought significant changes to management accounting information systems, particularly in providing faster, more accurate, and predictive information. The application of AI-supported management accounting information not only impacts the technical aspects of decision-making but also raises behavioral implications that influence managerial judgment and organizational performance. This study aims to systematically examine the behavioral implications of the use of AI-based management accounting information on managerial judgment processes and managerial performance. The method used is a literature review by examining relevant scientific articles from reputable international journals in the fields of management accounting, information systems, and organizational behavior. The results of the study indicate that AI support in management accounting can improve judgment quality by providing comprehensive data analysis, reducing certain cognitive biases, and increasing the speed and consistency of decisions. However, excessive reliance on AI systems also has the potential to create behavioral risks, such as decreased professional skepticism, overreliance on algorithmic recommendations, and a reduced role of intuition and managerial experience. These behavioral implications directly and indirectly affect managerial performance, both in terms of decision-making effectiveness, accountability, and the achievement of the organization's strategic goals. This research contributes to the development of management accounting literature by emphasizing the importance of a socio-technical approach to AI implementation, where technology integration needs to be balanced with an understanding of human behavioral factors to optimize performance benefits sustainably.